State of Private Tutoring in Mathematics Learning From School to Higher Education - Ojha, Lokraj (Innovative Research Journal, 2022)
The study aims to determine the state of private tutoring in mathematics learning from school to higher education in the Nepalese education system. Also, the study was intended to compare the practice of private tutoring in mathematics at the secondary level and higher education. The study was conducted within the framework of descriptive and qualitative research design using an interview schedule and observation guidelines as the tools for data collection. Finally, it was found that mathematics is one of the subject in which massive numbers of students demand for supplementary classes at secondary level and even in higher level. Intentionally, they want to join tuition classes at secondary level rather than primary level, and which level the board exam will be administered. Before beginning of semester system at University level those students majoring mathematics want to join private tuition classes to pass their examination. However, in present context, those students who are studying other faculties like management, science, technology demands for it than those who were majoring mathematics.